Environmental factors influencing the distribution of three species within the genus Persephona Leach, 1817 (Crustacea, Decapoda, Leucosiidae) in two regions on the northern coast of Sao Paulo State, Brazil - Pereira, Rafaela T. [UNESP] (2014)
Patterns of spatio-temporal distribution of Brachyura are determined by the interaction among life history traits, inter and intraspecific relationships, as well as by the variation of abiotic factors. This study aimed to characterize patterns of spatio-temporal distribution of Persephona lichtensteinii, Persephona mediterranea and Persephona punctata in two regions of the northern coast of Sao Paulo State, southeastern region of Brazil. Collections were done monthly from July 2001 to June 2003 in Caraguatatuba and Ubatuba, using a shrimp fishery boat equipped with double-rig nets. The patterns of species distribution were tested by means of redundancy analysis (RDA) and generalized linear mixed models (GLMM) in relation to the recorded environmental factors (BT: bottom temperature, BS: bottom salinity, OM: organic matter and granulometry (Phi)). The most influent environmental factor over the species distribution was the Phi, and the ascendant order of influence was P. lichtensteinii, P. punctata and P. mediterranea. The greater abundance of P. mediterranea showed a conservative pattern of distribution for the genus in the sampled region. The greater occurrence of P. punctata and P. lichtensteinii, in distinct transects than those occupied by P. mediterranea, seems to be a strategy to avoid competition among congeneric species, which is related to the substratum specificity.